Intake, growth performance and worm load in goat kids maintained on conventional soiled or raised wooden slatted floor - RAMACHANDRAN, N; SINGH, S P; TRIPATHI, M K; PAUL, SOUVIK; BHUSAN, SAKET; JINDAL, S K (The Indian Journal of Animal Sciences, 2017)
This experiment investigated the effect of raised wooden slatted floor (SLF) over conventional soil floor (SOF) on intake, growth, feed conversion efficiency (FCE) and worm load in goat kids under intensive stall system of feeding in semi-arid regions of India. Thirty post-weaned (4 months old) Jakhrana kids (10.2±0.09 kg) were radomly divided into two equal groups and assinged either to SLF or SOF group. Kids were reared up to 12 months of age, fed ad lib. roughage, green fodder and concentrate to meet nutrient requirements for optimum growth. Total gain and average daily gain (ADG) were similar between kids of SLF and SOF groups at 12 months. The ADG was 131.7 g in SLF and 122.0 g in SOF group. Dry matter intake per kg gain in SLF kids was 7.46 kg as compared to 7.72 kg in SOF kids with the overall feed efficiency of 13.40 and 12.95%, respectively were not different between two kid groups. The intake of organic matter, metabolizable energy and crude protein were similar between kid groups. The worm load in terms of coccidial oocysts, cestodes and nematodes eggs in faecal samples of SLF kids was significantly lower than SOF kids. The mean geometric faecal oocysts (GFOC) in SLF kids during first sampling period (March) was 2.5 times lower than SOF kids that reduced significantly on subsequent sampling periods. However, the GFOC was rather increased in SOF kids during second sampling and subsequently reduced during third and fourth sampling periods. The results indicated that the raised wooden slatted floor was effective in controlling coccidiosis, however, feed intake, growth performance and feed efficiency were not changed in kids reared under intensive system of production in semi-arid regions.